PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PENERAPAN ACTIVE LEARNING - Mulia Rahman; Muslem (Institut Ummul Quro Al-Islami Bogor, 2024)
Islamic Religious Education (PAI) is an important subject that can help students understand and practice Islamic teachings in their daily lives. Therefore, choosing a fun PAI learning strategy that encourages students to be proactive in this subject is important, so that the material presented by the teacher is absorbed by students. Here the role of the teacher is very urgent to create a lively classroom atmosphere, so that all students actively follow the lesson. For this, the application of an active learning strategy is one way to realize this. In order for the implementation of an active learning strategy to run well in schools/educational institutions, there are supporting factors in the implementation of active learning such as the commitment of PAI teachers in educating their students, high student enthusiasm for learning, and the role of the school (principal and staff) is very supportive of creating an active learning atmosphere. Likewise, the completeness of the facilities and infrastructure is one of the supporting factors for the smooth implementation of the active learning strategy. The role of teachers in implementing active learning can also not be maximized if there are school regulations that do not support change, limited teacher creativity in understanding active learning, there are teachers who do not plan learning as expected in the active learning strategy, there are teachers who still dominate the space in delivering material, and the lack of teachers in giving awards (rewards) to students.